Characterization of Nitrate Reductase from Light- and Dark-Exposed Leaves (Comparison of Different Species and Effects of 14-3-3 Inhibitor Proteins). - Lillo, C. (1997)
Nitrate reductase (NR) was extracted and partially purified from leaves of squash (Curcurbita maxima), spinach (Spinacia oleracea), and three transgenic Nicotiana plumbaginifolia leaves in the presence of phosphatase inhibitors to preserve its phosphorylation state. Purified squash NR showed activation by substrates (hysteresis) when prepared from leaves in the light as well as in darkness. A 14-3-3 protein known to inhibit phosphorylated spinach NR in the presence of Mg2+ decreased by 70 to 85% the activity of purified NR from dark-exposed leaves, whereas NR from light-exposed leaves decreased by 10 to 25%. Apparent lack of posttranslational NR regulation in a transgenic N. plumbaginifolia expressing an NR construct with an N-terminal deletion ([delta]NR) may be explained by more easy dissociation of 14-3-3 proteins from [delta]NR. Partially purified [delta]NR was, however, inhibited by 14-3-3 protein, and the binding constant of 14-3-3 protein (4 x 108 M-1) and the NR-inhibiting protein concentration that results in a 50% reduction of free NR (2.5 nM) were the same for NR and [delta]NR. Regulation of NR activity by phosphorylation and binding of 14-3-3 protein was a general feature for all plants tested, whereas activation by substrates as a possible regulation mechanism was verified only for squash.